2023
DOI: 10.1002/acn3.51766
|View full text |Cite
|
Sign up to set email alerts
|

Lorlatinib for ALK‐fused, infant‐type hemispheric glioma with lung metastasis: a case report

Abstract: Infant-type hemispheric glioma, a new subtype of pediatric high-grade glioma, arises in the cerebral hemispheres. Despite better survival outcomes, the treatment of infant-type hemispheric glioma is still facing challenges. Here, we reported a case of QKI-ALK fusion, infant-type hemispheric glioma with lung metastasis who achieved a complete clinical response after lorlatinib treatment. This typical case demonstrated the importance of appropriate molecularly targeted treatments in ALK-fused tumors, and lorlati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The detection of RTK fusion genes as hallmark molecular driver alterations not only fosters precise classification, but moreover bears the potential for targeted therapies involving RTK inhibition in IHG. Recently, multiple case studies reported significant responses in individual treatment attempts with lorlatinib, entrectinib and larotrectinib in ALK and ROS1 fusion positive IHG, potentially broadening the horizons of curative treatment options within a demographic peculiarly susceptible to severe sequela following conventional salvage treatment including extensive surgery or radiotherapy [ 9 , 30 36 ]. The suppression of tumor growth by MET inhibition in xenograft models of IHG has previously been demonstrated, and a substantial temporary treatment response in a patient harboring a MET fusion positive pediatric high-grade glioma treated with small molecule MET inhibitor crizotinib has been reported, whereby the appearance of further treatment-resistant lesions has been observed [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The detection of RTK fusion genes as hallmark molecular driver alterations not only fosters precise classification, but moreover bears the potential for targeted therapies involving RTK inhibition in IHG. Recently, multiple case studies reported significant responses in individual treatment attempts with lorlatinib, entrectinib and larotrectinib in ALK and ROS1 fusion positive IHG, potentially broadening the horizons of curative treatment options within a demographic peculiarly susceptible to severe sequela following conventional salvage treatment including extensive surgery or radiotherapy [ 9 , 30 36 ]. The suppression of tumor growth by MET inhibition in xenograft models of IHG has previously been demonstrated, and a substantial temporary treatment response in a patient harboring a MET fusion positive pediatric high-grade glioma treated with small molecule MET inhibitor crizotinib has been reported, whereby the appearance of further treatment-resistant lesions has been observed [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The combination was found to be only marginally effective, most likely due to secondary alterations in GBM genetics, such as MET amplification and alterations in PDGFR, PTEN, and/or STAT3 [ 47 ]. Currently, other EGFR inhibitors, such as lorlatinib, are being assessed for safety and efficacy in combination with TMZ for the treatment of metastatic brain tumors [ 70 ]. Perhaps these observations will facilitate designing a safer and potentially more effective dosing regimen for other EGFR inhibitors for clinical investigations in GBM patients [ 69 , 70 ].…”
Section: Approaches For Overcoming Tmz Resistance In Gbmmentioning
confidence: 99%
“…Currently, other EGFR inhibitors, such as lorlatinib, are being assessed for safety and efficacy in combination with TMZ for the treatment of metastatic brain tumors [ 70 ]. Perhaps these observations will facilitate designing a safer and potentially more effective dosing regimen for other EGFR inhibitors for clinical investigations in GBM patients [ 69 , 70 ].…”
Section: Approaches For Overcoming Tmz Resistance In Gbmmentioning
confidence: 99%